Modelling of Training Program Development for Supply Chain Management Business Project Development: Practical Research Results - Konstantinov, Igor; Fedotova, Marina A.; Bin, Yin (International Journal of Supply Chain Management, 2020)
Abstract- the article discusses the issues related to information-analytical support of the management/strategy development for international supply chain management business projects within training program development (level 2 of IEBP management model system): the selection of the key meta-competences , forms and formats of project-based learning, the most preferred for the main task types characteristic of the attractive activities, selected during HR-organization strategy development for IEBP management (they provide a brief description of the problem statement for this level). The article describes in detail the development of MAI-hierarchies (general preliminary and refined in VS-modification) developed for this level. They provide calculations of multi-expert assessments during the implementation of the supply chain management business project "New supply chain management", and analyze the main problems associated with the made choice made. A brief overview of additional (corrective) models of the supply chain management process optimization/rationalization is provided for this level. It was founded that governments around the world need to play a prominent role in developing strategies to protect supply chains for the future and put in place more robust disaster recovery plans, including relevant stockpiles, to enable more resilient outcomes.